Disseminated Talaromyces marneffei Infection With STAT3-Hyper-IgE Syndrome: A Case Series and Literature Review. (4th April 2023) - Li, Zhengtu; Yang, Jinglu; Qiu, Ye; Yang, Feng; Tang, Mengxin; Li, Shaoqiang; Zhan, Yangqing; Li, Yongming; Tang, Sufang; Jing, Cheng; Ye, Feng
Abstract: Background: Little is known about the clinical characteristics of talaromycosis with hyper–immunoglobulin E syndrome (HIES). Methods: We conducted a multicenter retrospective study, which included 7 hospitals from 2016 to 2022. Five consecutive cases of human immunodeficiency virus (HIV)–negative patients with systemic Talaromyces marneffei infections due to STAT3-HIES were identified. A systematic literature review of original articles published in English identified an additional 7 cases. Clinical characteristics and laboratory parameters were collected. Results: Forty-two percent (5/12) of patients were young adults. The main symptoms of 10 patients were similar: fever (75%), cough (75%) and dyspnea (33%), but two patients mainly had gastrointestinal symptoms. Most patients had a history of infections since infancy. T marneffei was cultured from the bronchoalveolar lavage fluid (50%) and 25% of patients were next-generation sequencing positive. Eight patients had significantly elevated serum immunoglobulin E, increased B cells and decreased natural killer cells. There were ten different STAT3 mutations, three of which were reported for the first time in this study. Chest computed tomography examinations showed multiple exudations with cavities in the lungs. Voriconazole combined with thymosin was effective. Despite given antifungal agents, most had poor outcomes and the case fatality rate was as high as 25%. Conclusions: STAT3-HIES is most likely a susceptibility factor for T marneffei infections among HIV-negative patients, which has a high case fatality rate. Increased awareness among clinicians is necessary to help in early diagnosis.